Systematic Variation in Yield Spreads for Tax-Exempt General Obligation Bonds - Benson, Earl D.; Kidwell, David S.; Koch, Timothy W.; Rogowski, Robert J. (Journal of Financial and Quantitative Analysis, 1981)
Earl D. Benson, David S. Kidwell, Timothy W. Koch, Robert J. Rogowski, Systematic Variation in Yield Spreads for Tax-Exempt General Obligation Bonds, The Journal of Financial and Quantitative Analysis, Vol. 16, No. 5 (Dec., 1981), pp. 685-702